Fractal Characteristics of the Seepage Erosion Process in Porous Soil - Yu Wang; Xiangbao Duan; Yanchang Gu; Shijun Wang (Geofluids)
Seepage-induced erosion in porous soil has always been a major concern in the field of geofluids. Various fractal models have been built to theoretically investigate the porosity and permeability coefficient. However, the seepage erosion process (i.e., incubation, formation, evolution, and destruction) in porous soil is not clearly demonstrated to clarify the seepage fractal characteristics. In this paper, a series of hydraulic tests were performed to reveal the mass fractal characteristics of sandy gravels, coarse-grained sands, and fine-grained sands in the seepage erosion process. The results show that the mass fractal dimension was appropriate to describe the cumulative mass distribution of particles, the complexity of pore networks, and the dynamic changes of the seepage erosion process. Moreover, the scale-invariant interval, as an essential precondition for the accurate calculation of the mass fractal dimension, was to some extent affected by the average grain size and the fine content of porous soil. In particular, the changing trend of porosity and permeability coefficient with the mass fractal dimension was demonstrated in the seepage erosion process. Both porosity and permeability coefficients indicated an increasing trend as the development of seepage erosion. However, the mass fractal dimension gradually decreased due to the removal of fine particles induced by seepage flow water. Research findings will not only provide a new perspective on the seepage erosion mechanism but also predict the development of the seepage erosion process in engineering practice.